(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article the author deals with the problem of effectiveness of educational process in the higher educational establishment with the help of the development of the ability to self-regulation activity. The aspects of improvement of educational and professional activity of students are given, taking into consideration the role of self-regulation ability in this process. It is indicated, that the use self-regulation ability of activity will lead to the realized forming of personality, activity in searches and acquiring new knowledges and methods of activity, self-realizing of personality, own qualities and deeds, that will help personality to expose him and inner world, preparedness to self-development, to social and individual responsibility, eagerness to the realized independent choice, the best result.